Angiosperm flora of Satchari National Park, Habiganj, Bangladesh - Arefin, Md. Kamrul; Rahman, Md. Mizanur; Uddin, Mohammad Zashim; Hassan, Md. Abul (Bangladesh Journal of Plant Taxonomy, 2011)
An inventory of angiosperm flora of Satchari National Park, located in Habiganj district, is prepared on the basis of collected materials and observation made from November 2008 to December 2009. From the study site, 245 angiosperm species including cultivated and planted in 183 genera under 72 families are documented. Of 245 species recorded here, 86 species are represented by herbs, 46 by shrubs, 73 by trees, 37 by climbers and 3 by epiphytes. The survey has also confirmed the occurrence of seven threatened angiosperm species, one tree fern and one gynosperm in the Park area. For each species scientific name, local name (wherever available), family, habit and habitat are provided with citation of specimens. Keywords: Checklist; Angiosperms; Satchari National Park. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9298 Bangladesh J. Plant Taxon. 18(2): 117-140, 2011 (December)